Cyanobacteria as Cell Factories to Produce Plant Secondary Metabolites - Xue, Yong; He, Qingfang (Frontiers in Bioengineering and Biotechnology, 2015)
Cyanobacteria represent a promising platform for the production of plant secondary metabolites. Their capacity to express plant P450 proteins, which have essential functions in the biosynthesis of many plant secondary metabolites, make cyanobacteria ideal for this purpose, and their photosynthetic capability makes it possible to eliminate expensive carbohydrate feedstocks from the culture medium. This review summarizes the advantages of using cyanobacteria to transgenically produce plant secondary metabolites. Some techniques to improve heterologous gene expression in cyanobacteria are discussed.